2017
DOI: 10.1039/c7ra04889k
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(iii)-catalyzed indole-directed carbenoid aryl C–H insertion/cyclization: access to 1,2-benzocarbazoles

Abstract: A rhodium(iii)-catalyzed indole-directed aryl C–H bond carbenoid insertion cascade of 2-arylindoles with diazo compounds has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Deuterium was observed at both ortho -positions of phenyl ring (68%) and C3 position of indole ring (74%) when the reaction was carried out in the absence of 2 using DCE/CD 3 OD as the solvent (Scheme c). The H/D exchange of ortho -positions of the phenyl ring indicated that the reaction underwent coordination of nitrogen, and the H/D exchange of the indole ring may be due to the strong nucleophilic property of C3-position which easily attacks rhodium cation followed by metal protonation . Another control experiment showed that no deuterium exchange at the ortho -positions of the phenyl ring was seen in the absence of a rhodium catalyst (Scheme d), suggesting that the rhodium catalyst is essential for this reaction.…”
supporting
confidence: 57%
“…Deuterium was observed at both ortho -positions of phenyl ring (68%) and C3 position of indole ring (74%) when the reaction was carried out in the absence of 2 using DCE/CD 3 OD as the solvent (Scheme c). The H/D exchange of ortho -positions of the phenyl ring indicated that the reaction underwent coordination of nitrogen, and the H/D exchange of the indole ring may be due to the strong nucleophilic property of C3-position which easily attacks rhodium cation followed by metal protonation . Another control experiment showed that no deuterium exchange at the ortho -positions of the phenyl ring was seen in the absence of a rhodium catalyst (Scheme d), suggesting that the rhodium catalyst is essential for this reaction.…”
supporting
confidence: 57%
“…In this regard, an NH indole moiety turned out to be a good directing group for the rapid construction of diverse indole-fused heterocyclic scaffolds. For instance, Rh­(III)-catalyzed annulation reactions of 2-aryl-1 H -indoles with alkynes, carbon monoxide, alkenes, ketenes, sulfoxonium ylides, and diazo compounds have been well established for the selective synthesis of five- and six-membered indole-fused heterocycles. In contrast, there are only few reports on the construction of bridged medium-sized skeletons through a Rh­(III)-catalyzed annulation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the NH indole moiety has emerged as a versatile functionalizable directing group for the synthesis of various indole-containing polycyclic compounds. For example, NH indole-directed oxidative annulations of 2-arylindoles with different coupling partners, such as diazo compounds, sulfoxonium ylides, ketenes, carbon monoxide, alkynes, or alkenes, could be successfully utilized for the selective synthesis of benzocarbazole, isoindoloindolone, indoloisoquinoline, or isoindoloindole derivatives (Scheme ). On the contrary, Rh­(III)- or Ir­(III)-catalyzed C–H functionalization reactions using benzoquinone as a coupling partner have been used in the direct construction of several hard-to-prepare cyclic skeletons reported by Xu, Wang, and Ison’s groups .…”
mentioning
confidence: 99%